Antimicrobial Activity of Kluwek (Pangium edule) Seed Extract as Natural Preservatives of Tuna Fish Ball - Christine Fransin Mamuaja; Frans Lumoindong (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Kluwek seeds (Pangium edule) contain antimicrobial compounds that can be categorized as preservativeagents. The main objective of this study was to evaluate the effect of the addition of kluwek seeds extractagainst microbiological quality, sensory quality and shelf life of tuna fish balls. This study applied a factorialcompletely randomized design with various extract concentrations and storage duration treatments, eachof which conducted in triplicate. In this study, the fishballs were immersed in 2%, 4%, 6% and 8% b/vextract for 60 minutes, then stored for three days at room temperature (28-30ºC). The results showed thatthe the highest inhibitory activity against microbial growth was exhibited by meatballs immersed in 8%concentration, in which total microbial load up to the third day storage was 1,32 x 102 CFU/g which wasin the INS range of quality for fish ball (1 x 107). Fishballs without storage (0 day) was more acceptable bypanelists when compared to fishballs from 1, 2, and 3 days storage in terms of organoleptic acceptability.Fishballs were still accepted organoleptically only until one day storage, while fishballs stored for 2 and 3days have deteriorated based on visual observation of the color, odor, taste and texture.